The Role of Online Psychotherapy in COVID-19: An Evidence Based Clinical Review - Hamzah Shatri; Oryza Gryagus Prabu; Erpryta Nurdia Tetrasiwi; Edward Faisal; Rudi Putranto; Raden Irawati Ismail (Interna Publishing, 2021)
Background: COVID-19 is an infectious disease that is easily widespread and has clinical manifestations as mild, moderate, or severe disease. COVID-19 patients are required to be isolated during treatment to reduce transmission. This can cause anxiety and depression, which in turn worsens the patient's illness. Providing supportive psychotherapy can help provide a feeling of safety, comfort and calm for patients. The choice of method in providing supportive psychotherapy can be done online/teleconsultation or internet-based. This clinical review aims to determine the effect of online teleconsultation or internet-based psychotherapy on COVID-19 patients. Methods: A systematic search was performed using online databases, such as PubMed, Cochrane, EBSCO/CINAHL and ProQuest. The identified articles were screened using eligibility criteria. There were 2 studies (Zhou et al, and Wei et al) which were analyzed critically using the Newcastle Ottawa Scale. Results: Both studies showed that management of psychotherapy through teleconsultation or internet-based on COVID-19 patients can help relieve the patient's psychological symptoms. Zhou et al studied 63 suspected COVID-19 with 23.8% (n = 15) having a Hospital Anxiety Depression Scale (HADS) score of 8 or more. There was a significant decrease in HADS-A nxiety (HADS-A) scores (p <0.01) and HADS-Depression (HADS-D) scores (p <0.01) in 15 patients, and from the overall HADS scores (p < 0.01). Wei et al. Showed 17-HAMD and HAMA scores in the online psychological intervention group also showed a significant reduction in symptoms of depression and anxiety compared to controls. Conclusion: Psychotherapy through online teleconsultation or internet-based on COVID-19 patients can help relieve symptoms of anxiety and depression and teleconsultation and also effective in dealing with psychological complications in patients with COVID-19.